SPECIFIC FEATURES OF ANESTHESIA IN PATIENTS WITH LIVER FAILURE (International journal of medical sciences, 2026)
Liver failure represents a complex clinical condition characterized by profound metabolic, hemodynamic, and hematological disturbances that significantly influence perioperative management. Because the liver is central to drug metabolism, protein synthesis, coagulation regulation, immune modulation, and maintenance of systemic homeostasis, hepatic dysfunction creates substantial challenges for anesthesiologists. Altered pharmacokinetics and pharmacodynamics, reduced hepatic blood flow, portal hypertension, ascites, renal dysfunction, and susceptibility to encephalopathy increase perioperative morbidity and mortality. The selection and titration of anesthetic agents require careful consideration of reduced metabolic capacity and altered protein binding. Furthermore, perioperative stress may precipitate hepatic decompensation in vulnerable patients. This article provides a comprehensive and clinically oriented review of pathophysiological alterations in liver failure and discusses evidence-based strategies for preoperative risk stratification, intraoperative anesthetic management, coagulation correction, fluid therapy, and postoperative monitoring. An individualized, multidisciplinary, and physiology-driven approach is essential to optimize outcomes in this high-risk population.